THE STUDY OF ETHNONYMS IN BALOCHISTAN: THE STUDY OF ETHNONYMS IN BALOCHISTAN - Khan, Fouzia Rehman; Zaidi, Najia; Abbas, Sohila (Hanken, 2018)
The present study lies in the field of Onomastic, with specific exploration of the prevalence of Ethnonyms that deals with the mention of ethnicity as a suffix to the first name through naming practices in the province of Balochistan. The study aims at explicating the reasons as to why or why not the people of Balochistan express their Baloch ethnic identity with their names and naming practices. A qualitative paradigm of research guided the methodology of this study with data collection done through semi-structured interviews and open ended questionnaires by the selected participants who belonged to different caste and clans of Baloch community. The interpretation and analysis of the data reveals that because of the tribal set up of the province a large number of its residents attach the name of their caste or tribe with their first name for multiple reasons such as considering the expression of ethnic identity as an essential element in a multilingual multi-ethnic society. This practice is taken as a matter of pride. It gives them sense of security and it is sometimes used for social and political gains. It also earns them the loyalty of their group. It unifies and binds them to a single ethnicity. The data The Study of Ethnonyms in Balochistan revealed that there are very few people who do not use ethnic suffix and deem the practice as unimportant. The study concludes that the naming practice in Balochistan is based on ethnonyms for centuries and the practice will continue due to its association with social esteem and cultural pride